Esophageal Atresia Associated with Congenital Duodenal Obstruction: Turkish Esophageal Atresia Registry (TEAR) Evaluation - Durakbaşa, Çiğdem Ulukaya; Soyer, Tutku; İlhan, Hüseyin; Oztan, Mustafa Onur; Uzunlu, Osman; Firinci, Binali; Özcan, Rahşan; Oral, Akgun; Ciftci, Ilhan; Ozcakir, Esra; Akkoyun, Ibrahim; Güney, Doğuş; Ozden, Onder; Gul, Cengiz; Ozcan, Coskun; Parlak, Ayse; Aydın, Emrah (European Journal of Pediatric Surgery, 2023)
Introduction Coexistent congenital duodenal obstruction and esophageal atresia (EA) is known to have significant morbidity and mortality. Management strategies are not well-defined for this association. The data from the Turkish EA registry is evaluated.Materials and Methods A database search was done for the years 2015 to 2022.Results Among 857 EA patients, 31 (3.6%) had congenital duodenal obstruction. The mean birth weight was 2,104 (± 457) g with 6 babies weighing less than 1,500 g. Twenty-six (84%) had type C EA. The duodenal obstruction was complete in 15 patients and partial in 16. Other anomalies were detected in 27 (87%) patients. VACTERL-H was present in 15 (48%), anorectal malformation in 10 (32%), a major cardiac malformation in 6 (19%), and trisomy-21 in 3 (10%). Duodenal obstruction diagnosis was delayed in 10 (32%) babies for a median of 7.5 (1–109) days. Diagnosis for esophageal pathologies was delayed in 2. Among 19 babies with a simultaneous diagnosis, 1 died without surgery, 6 underwent triple repair for tracheoesophageal fistula (TEF), EA, and duodenal obstruction, and 3 for TEF and duodenal obstruction in the same session. A staged repair was planned in the remaining 9 patients. In total, 15 (48%) patients received a gastrostomy, the indication was long-gap EA in 8. Twenty-five (77%) patients survived. The cause of mortality was sepsis (n = 3) and major cardiac malformations (n = 3).Conclusion Congenital duodenal obstruction associated with EA is a complex problem. Delayed diagnosis is common. Management strategies regarding single-stage repairs or gastrostomy insertions vary notably depending on the patient characteristics and institutional preferences.
Keywords: esophageal atresia; duodenal atresia; management; surgery; outcome